Preparation and Properties of Indium Ion Modified Graphite Felt Composite Electrode - Su, Yang; Chen, Na; Ren, Hai-lin; Guo, Li-li; Li, Zhen; Wang, Xiao-min (Frontiers in Chemistry, 2022)
Iron-chromium redox flow batteries (ICRFBs) have the advantages of high safety, long cycle life, flexible design, and low maintenance costs. Polyacrylonitrile-based graphite felt composite material has good temperature resistance, corrosion resistance, large surface area and excellent electrical conductivity, and is often used as the electrode material of ICRFB, but its chemical activity is poor. In order to improve the activity of the graphite felt electrode, In3+ was used for modification in this paper, and the modified graphite felt was used as the electrode material for iron-chromium batteries. The structure and surface morphology of the modified graphite felt were analyzed by specific surface area analyzer and scanning electron microscope; the electrochemical impedance spectroscopy and cyclic voltammetry experiments were carried out on the electrochemical workstation to study the electro catalytic activity of In3+ modified graphite felt and its performance in ICRFBS. The results show that the graphite felt electrode modified with a concentration of 0.2M In3+ was activated at 400 ℃ for 2 hours, and its surface showed a lot of grooves, and the specific surface area reached 3.889m2/g, while the specific surface area of the untreated graphite felt was only 0.995m2/g significantly improved. Electrochemical tests show that the electrochemical properties of graphite felt electrodes are improved after In3+ modification. Therefore, the In3+ modified graphite felt electrode can improve the performance of ICRFB battery, and also make it possible to realize the engineering application of ICRFB battery.